TECHNOLOGICAL INNOVATION FROM ENTERPRISE INCUBATORS: PHENOMENOLOGY FOR TWO DEVELOPING COUNTRIES - ARGOTA-PÉREZ, George (2023)
The study aimed to analyze innovation from business incubators. A survey was applied to six consultants from the Republic of Cuba and twelve university professors from the Republic of Peru, where it was structured using a Likert scale, six indicators for analysis: 1st) technological social prospective service, 2nd) mental map and decisions to run, 3rd) research and development strategy, 4th) coding of technological innovations, 5th) value of business creativity, and 6th) entrepreneurship analysis. Validation was through Cronbach’s alpha coefficient. It was observed that at least three questions were not accepted by the respondents representing 80%. The value of the Likert-type scale was 2.88, which meant irregular responses to the knowledge of the variable’s social communication, innovation, and business incubation. The value of Cronbach’s alpha coefficient was 0.66, with good reliability. The results indicated limitations on the knowledge that is related to social management, the thinking model from social communication towards innovation and decisions according to the mental map that is oriented to business incubators.